Effect of Rizatriptan and Other Triptans on the Nausea Symptom of Migraine: A Post Hoc Analysis - Lipton, Richard B.; Pascual, Julio; Goadsby, Peter J.; Massiou, Helene; McCarroll, Kathleen A.; Vandormael, Kristel; Jiang, Kaihong; Lines, Christopher R. (Headache, 2001)
Objective.—To compare the effects of oral rizatriptan, sumatriptan, naratriptan, and zolmitriptan on the relief and emergence of nausea during a migraine attack. Methods.—Data from five randomized, placebo‐controlled, double‐blind clinical trials in which oral rizatriptan 10 mg was directly compared with oral sumatriptan 100 mg (N = 772), 50 mg (N = 1168), 25 mg (N = 1180), naratriptan 2.5 mg (N = 406), or zolmitriptan 2.5 mg (N = 571) for the acute treatment of a migraine attack were retrospectively analyzed. Migraine was diagnosed according to International Headache Society criteria. Presence or absence of nausea was recorded at baseline and at 0.5, 1, 1.5, and 2 hours after dosing. The end points analyzed were relief of nausea in those who had it at baseline and emergence of nausea in those who were free of it at baseline. Treatments were compared using odds ratios estimated from logistic regression models at 2 hours, and averaged odds ratios for the first 2 hours posttreatment. Results.—Approximately 60% of patients in each treatment group had nausea at baseline. In those patients with nausea at baseline, significantly more patients treated with rizatriptan 10 mg were free of nausea at 2 hours compared with sumatriptan 100 mg (66% versus 58%, P = .043), sumatriptan 50 mg (68% versus 57%, P = .010), sumatriptan 25 mg (68% versus 59%, P = .017), and naratriptan 2.5 mg (59% versus 45%, P = .014). Averaging over the four posttreatment time points in the first 2 hours, significantly more patients treated with rizatriptan 10 mg were free of nausea compared with sumatriptan 100 mg (P = .004), sumatriptan 50 mg (P = .001), and naratriptan 2.5 mg (P = .015). No significant differences in nausea relief were seen between rizatriptan 10 mg and zolmitriptan 2.5 mg, either at 2 hours (65% versus 61%, P = .210) or over the first 2 hours (P = .781). Rates of treatment‐emergent nausea at 2 hours ranged from 11% to 18% with placebo, from 5% to 13% with rizatriptan 10 mg, and from 10% to 20% with other comparator triptans. Conclusions.—Oral rizatriptan 10 mg was more effective than oral sumatriptan and naratriptan at eliminating nausea within 2 hours in patients who had it at baseline. Rates of emergent nausea in patients who were free of it at baseline were low, and no consistent differences were observed between active treatments.